MANAJEMEN PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PENDIDIKAN ISLAM: STUDI KASUS DI SMA NEGERI 3 BATUSANGKAR - Emi Afnida (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
Developmen Management  of Human Resources in Islamic Educational: Case Study In SMA 3 Batusanggkar. The background of this research is the phenomenon of the existence of SMA Negeri 3 Batusanggkar which is a superior school in Tanah Datar . This school is one of the top schools very enthused by the Tanah Datar district because the school was able to create a quality output. This research focus school management excels in developing Islamic education resources in SMA Negeri 3 Batusanggkar, while the sub-focus is the planning , organizing, directing and monitoring in SMA Negeri 3 Batusanggkar. The purpose of this study was to determine the in-depth implementation of the implementation of school management excels in improving Islamic education resources, to know what programs are being developed to improve educational resources and how the application of the conditioning or habituation - cultural school in SMAN 3 Batusanggkar.From the research findings it can be concluded ahead of school management in developing the resources of Islamic education in SMA Negeri 3 Batusanggkar has done well but needs further development by running a key factor of all is hard work, smart work, exemplary, habituation and consistent cooperation between schools with parents, community and educational staff.Kata Kunci:  sumber daya manusia, pendidikan islam